Penguatan Kelembagaan dan Tata Kelola Pokdarwis Ceria di Desa Wisata Wae Lolos - Laurensius Sandrio; Septian Hutagalung; Roseven Rudiyanto; Marius Yosef Seran (Jurnal Abdimas Pariwisata, 2024)
Institutional Strengthening and Governance of Pokdarwis Ceria in Wae Lolos Tourism Village Wae Lolos Village is a Tourism Village located in Sano Nggoang District. The Wae Lolos Tourism Village community already has a Ceria Tourism Awareness Group (Pokdarwis) as a concrete form of community participation in tourism development in the Tourism Village. However, the problem faced by Wae Lolos Village for tourism development is the lack of community knowledge and experience in the tourism sector. Moreover, the absence of a framework is one of the factors in the failure of the development of tourist destinations with the concept of Community Based Tourism (CBT). Departing from this phenomenon, this activity aims to directly answer the problems as previously explained, through the transfer of knowledge and technical skills from educational institutions to the community in the Ceria tourism awareness group in the Wae Lolos tourism village using lecture, discussion and discussion methods. practice. The result of this activity is that the community not only understands that developing a tourism village requires the active participation of the community, but is also able to make tour packages.